INDIA’S HOSTILITY TO INTERNATIONALIZE CRIMINAL JUSTICE- CALCULATIVE STRATEGY OR PREJUDICED RELUCTANCE? - Tiwari, Garima (European Scientific Journal, ESJ, 2014)
On May 31, 2013 United Nations urged India to institute a commission of inquiryserving as a transnational justice mechanism, into extra-judicial killings in its North-eastern states. Urging India to repeal the controversial Armed Forces Special Powers Act, 1958, United Nations also asked India to ensure that the legislation regarding the use of force by the armed forces provides for the respect of the principles of proportionality and necessity. Various reports have shown that the State violence in Kashmir and North Eastern States of India was institutionalized through a culture of institutional impunity to the state forces which perpetuate the state of human rights violations. India has not acceded to the Rome Statute. It abstained in the vote adopting the statute in 1998, saying it objected to the broad definition adopted of crimes against humanity, the right given to the Security Council to refer cases, delay investigations and bind non-State Parties, and the use of nuclear weapons or other weapons of mass destruction not being explicitly outlawed. Even though, India has ratified the Geneva Conventions, it has decided to overlook Common Article 3. In light of the above, this paper highlights why the emerging power India, abstains from joining the Rome Statute and the possibility of India being brought under the scanner of International Criminal Court.